2008
DOI: 10.1162/jocn.2008.20.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Contextual Representation for Objects' Identities and Their Locations

Abstract: Visual context plays a prominent role in everyday perception. Contextual information can facilitate recognition of objects within scenes by providing predictions about objects that are most likely to appear in a specific setting, along with the locations that are most likely to contain objects in the scene. Is such identity-related ("semantic") and location-related ("spatial") contextual knowledge represented separately or jointly as a bound representation? We conducted a functional magnetic resonance imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 74 publications
7
65
1
Order By: Relevance
“…Dell, 1986; Dell et al, 1997; Humphreys et al, 1988; Levelt, 1989; Mirman, 2011). In the fMRI experiment (Experiment 1), we found evidence that short-term adaptation to animal pictures transferred significantly more to visually and conceptually related objects in the left lateral frontal cortex when the adapted anchor picture was named several times prior to the fMRI experiment (see also Gronau et al, 2008, for similar results). The degree to which this tuning change occurred was directly related to the proportion of conceptual errors that participants made in the picture naming sessions just before and after the fMRI scanning session.…”
Section: Discussionmentioning
confidence: 58%
“…Dell, 1986; Dell et al, 1997; Humphreys et al, 1988; Levelt, 1989; Mirman, 2011). In the fMRI experiment (Experiment 1), we found evidence that short-term adaptation to animal pictures transferred significantly more to visually and conceptually related objects in the left lateral frontal cortex when the adapted anchor picture was named several times prior to the fMRI experiment (see also Gronau et al, 2008, for similar results). The degree to which this tuning change occurred was directly related to the proportion of conceptual errors that participants made in the picture naming sessions just before and after the fMRI scanning session.…”
Section: Discussionmentioning
confidence: 58%
“…At the same time, visual object processing appears to activate action representations, even in tasks not involving a motor response (e.g., Kalénine, Mirman, Middleton, & Buxbaum, 2012; Lee et al, 2013; Myung et al, 2010). Additionally, visual context influences object processing (e.g., Gronau, Neta, & Bar, 2008; Mudrik, Lamy, & Deouell, 2010). In objects associated with more than one action, such as the conflict objects presented here, we may speculate that the visual context serves to amplify the action associated with it (e.g., Wurm, von Cramon, & Schubotz, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…An emerging body of anatomical and imaging experiments suggests rapid magnocellular pathways to prefrontal cortex can prime object categories or contexts that aid in rapid object and scene recognition (Bar et al, 2006; Gronau, Neta, & Bar, 2008; Kveraga, Boshyan, & Bar, 2007). Recent electrophysiology studies in V4 have found that, in addition to contrast gain due to spatial attention, there is also independent feature-based attention that modifies spectral tuning of preferred spatial frequencies (David, Hayden, Mazer, & Gallant, 2008; Hayden & Gallant, 2005, 2009).…”
Section: Discussionmentioning
confidence: 99%